La participación de la familia y su vinculación en los procesos de aprendizaje de los niños y niñas en contextos escolares (2013)
The new educational scenarios asking for quality and equity, are positioning the Family-School relationship as a key piece, because if it develops in a positive way, will be a potential for mutual cooperation, promoting significative learning in the students. This relationship is analyzed from an eco-systemic view, which allows articulated in different ecological levels, the dimensions of: School, Family and Learning. From this analysis comes the Process of Parental Involvement, as a strategic feature to improve learning, the school climate and contribute to the educative improvement. Finally, it presents some strategies targeted to promote diverse instance of participation and it develops some considerations to help design and implement strategy of Parental Involvement in the school.